DIE ONTSTAAN EN DIE ONTWIKKELING VAN DIE SKOOLKADETTE-STELSEL IN DIE RSA: GREPE UIT DIE GESKIEDENIS EN 'N OORSIG OOR DIE HUIDIGE STELSEL - Viljoen, M.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
The origin and development of the school cadet system in the Republic of South Africa is dealt with in this article. A historical revue is furnished as well as a perspective of the present system